Countryside Education and Psychology: possibilities and limitations of dialogs engaged in the fight for rights - Maria Isabel Antunes-Rocha; Marcelo Loures (Universidade Federal do Norte do Tocantins, 2021)
Psychology, as a science, is linked to each time/place where it produces and reproduces its theoretical and practical references. In that sense, it can be said that its presence in the discussion about providing schools to peasant populations carries the marks of the dispute between the projects of school, countryside and society in each period of history. This article is an effort to identify and discuss the academic productions that articulate Psychology with Countryside Education and Rural Education. For the development of the research, references were sought in papers from the SciELO platform and the database of CAPES' dissertations and theses. During the stage of systematization and analysis of the material, it can be observed that, among other results obtained, Psychologists have been concerned with adapting and/or recreating theories to interact with educational issues in the countryside, and that, these days, peasant individuals have taken over the authorship of the research produced, playing a leading role in the production of knowledge about their lives. As a conclusion, the data obtained seem to point to the presence of the interaction with theoretical frameworks considered as critical in Psychology, as well as the emergence of new theoretical possibilities such as the formulation of the perspective of Social Representations in Motion.